Изменчивость размеров инкапсулированных рецепторов суставов грудной конечности млекопитающих - Ильенко, H.H; Сопин, Л.В. (Вестник зоологии, 1980)
Linear variability was studied in 1915 incapsulated receptors of limb joints in three main adaptive mammalian groups. It is shown that variability of the same forms of incapsulated receptors in different components of the joint is different. The highest scope of incapsulated joint receptors variability is observed in unguligrades. Variability of the same receptors in the phyllogenetically similar species is the same.